2018
DOI: 10.1272/jnms.2018_85-7
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Verrucous Carcinoma: Revisiting the Definition

Abstract: Verrucous carcinoma (VC) is an uncommon, distinct type of well-differentiated squamous cell carcinoma. Here we present two cases of VC, one arising from the lower leg and the other from genital skin.Case 1, a female patient, aged 95 years, had a brownish verrucous plaque on her right lower leg. Histopathologically, epithelial tumor cells grew pushing the stroma, while the basement membrane was intact. No prominent cellular atypia or hyperchromatin was found. Case 2, a male patient, aged 53 years, had a verruco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…We reviewed 26 publications with a total of 115 patients with CVC and found that 19 patients recurred with a prevalence of 16.5% and a mean age of 59.6 years (range 38-91), 16 of whom (16/19,84.2%) within 2 years (2, 24 months) after surgery, however, one patient recurred at 26 months after surgery, and two patients were not available. 4 -6,11,12,15,27,30,35,36,42,47,49,62,68,73,74,77,84 -91 Of the recorded data on recurrence, there were 10 cases in men (10/16, 62.5%) and 6 cases in women (6/16, 37.5%). The majority (10/19 patients) of the recurrent cases were located on the foot, one each on the lower leg, axilla, ankle, and hand, in addition to five cases not documented.…”
Section: Prognosismentioning
confidence: 99%
“…We reviewed 26 publications with a total of 115 patients with CVC and found that 19 patients recurred with a prevalence of 16.5% and a mean age of 59.6 years (range 38-91), 16 of whom (16/19,84.2%) within 2 years (2, 24 months) after surgery, however, one patient recurred at 26 months after surgery, and two patients were not available. 4 -6,11,12,15,27,30,35,36,42,47,49,62,68,73,74,77,84 -91 Of the recorded data on recurrence, there were 10 cases in men (10/16, 62.5%) and 6 cases in women (6/16, 37.5%). The majority (10/19 patients) of the recurrent cases were located on the foot, one each on the lower leg, axilla, ankle, and hand, in addition to five cases not documented.…”
Section: Prognosismentioning
confidence: 99%